2022
DOI: 10.1186/s12951-022-01560-0
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-mimicking Mn–Cu hybrid nanoflowers for paper-based visual detection of phenolic neurotransmitters and rapid degradation of dyes

Abstract: Background Laccase-based biosensors are efficient for detecting phenolic compounds. However, the instability and high cost of laccases have hindered their practical utilization. Results In this study, we developed hierarchical manganese dioxide–copper phosphate hybrid nanoflowers (H–Mn–Cu NFs) as excellent laccase-mimicking nanozymes. To synthesize the H–Mn–Cu NFs, manganese dioxide nanoflowers (MnO2 NFs) were first synthesized by rapidly reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Laccase is a polyphenol oxidase that can oxidize a wide range of substrates while reducing dioxygen to water and has been considered as a green biological tool for the degradation of various phenolic and non-phenolic contaminants. Previous studies have revealed that laccase can catalyze the oxidation of AFB 1 to aflatoxin Q 1 (AFQ 1 ) in aqueous solution. , The toxicological analysis illustrated that AFQ 1 was almost non-toxic to human liver cells . However, the detoxification efficiency for non-phenolic compounds is poor as a result of the low redox potential (0.5–0.8 V) of laccase .…”
Section: Resultsmentioning
confidence: 99%
“…Laccase is a polyphenol oxidase that can oxidize a wide range of substrates while reducing dioxygen to water and has been considered as a green biological tool for the degradation of various phenolic and non-phenolic contaminants. Previous studies have revealed that laccase can catalyze the oxidation of AFB 1 to aflatoxin Q 1 (AFQ 1 ) in aqueous solution. , The toxicological analysis illustrated that AFQ 1 was almost non-toxic to human liver cells . However, the detoxification efficiency for non-phenolic compounds is poor as a result of the low redox potential (0.5–0.8 V) of laccase .…”
Section: Resultsmentioning
confidence: 99%
“…However, the inappropriate disposal of wastewater is a big challenge that disturbs all aquatic environments in the whole world. Wastewater containing phenolic compounds affects humans and other organisms for their high toxicity [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other systems, the Cu metals-based encapsulation of laccases via metal-protein hybrids is beneficial to retain better residual activity due to the presence of Cu as an active center in laccase [ 16 , 23 , 32 ]. In addition, Cu-based hybrids also exhibit laccase-mimicking properties and are helpful in the degradation of phenolics [ 33 , 34 ]. However, the Cu-containing magnetic NPs have never been used to immobilize laccase covalently.…”
Section: Introductionmentioning
confidence: 99%